2016
DOI: 10.3174/ajnr.a4994
|View full text |Cite
|
Sign up to set email alerts
|

Impact of MR Neurography in Patients with Chronic Cauda Equina Syndrome Presenting as Chronic Pelvic Pain and Dysfunction

Abstract: MR neurography impacts the diagnosis and therapeutic management of patients with suspected chronic cauda equina syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Diagnosis should be based on histopathological findings because the presence of spinal nerve root fibers in the wall or cavity of the cyst are required for confirmation. However, magnetic resonance neurography has been recently proposed for diagnosis [7]. In our case, histopathology was not performed because non-surgical treatment was effective in relieving the associated neuralgia; but, results of the imaging studies supported our diagnosis.…”
Section: Discussionmentioning
confidence: 60%
“…Diagnosis should be based on histopathological findings because the presence of spinal nerve root fibers in the wall or cavity of the cyst are required for confirmation. However, magnetic resonance neurography has been recently proposed for diagnosis [7]. In our case, histopathology was not performed because non-surgical treatment was effective in relieving the associated neuralgia; but, results of the imaging studies supported our diagnosis.…”
Section: Discussionmentioning
confidence: 60%
“…Acute or sub-acute compressive CES is a surgical emergency. With the recognition of DLMs, much literature will have to be revised appropriately [960][961][962][963]. Chronic CES from iatrogenic LMF is very distressing to patients, particularly those moving in and out of bowel and bladder sphincter control with disease fluctuation, but is not a surgical emergency [963,964] unless there is colonic atonia and the patient is in danger of ruptured bowel, or a similar life threatening condition-in which case the condition is the emergency, not the cauda equina.…”
Section: Is Chronic Cauda Equina Syndrome (Ces) From Dlms ± Flare Con...mentioning
confidence: 99%
“…Results of recent use of intra-SAS neuroendoscopic lysis of adhesions are awaited. Educational emergency "self-help plans," appropriate supplies (self-catheter for urine, gloves for manual stool removal), training on how to use them, and a steroid pack if they respond to steroids helps patients manage at home [961,963,965].…”
Section: Plos Onementioning
confidence: 99%
“…Fortunately, a growing number of clinical studies are published, recently. These studies showed promising results that the MRN played an important role in diagnostic certainty and treatment decision-making ( 46 47 49 51 52 ). However, most of the studies were retrospective, and inevitably biased to positive side.…”
Section: Discussionmentioning
confidence: 99%